FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KONSUMEN PADA USAHA BITE & CO. CAFÉ LAMPRIT BANDA ACEH - Indri Nurul Mutia; Husnaina Mailisa Safitri (universitas teuku umar, 2018)
ABSTRACT The purpose of this research are to examine the influence of price, Word of Mouth and location towards Customers purchasing decisions at Bite & CO. Café Banda Aceh both parcially and simultaneously. The research method by describing clearly on the research objects. The research data gathered through questionnaire list and interview. The hypothesis test uses double linear regression analysis on trust level 95% (α = 0,05). The result of this research feasibility test model by using t-test (partial) shows that price, Word of Mouth and location significantly influence customers purcasing decisions. And using F-test (Simultaneously), it shows that price, Word of Mouth and location significantly influence customers purchasing decisions at Bite & CO. Café Banda Aceh as well. Keywords : Price, Word of Mouth, location, Customers Purchasing Decisions, Bite & Co. Café